2018
DOI: 10.1371/journal.pgen.1007750
|View full text |Cite
|
Sign up to set email alerts
|

Synaptogyrin-2 influences replication of Porcine circovirus 2

Abstract: Porcine circovirus 2 (PCV2) is a circular single-stranded DNA virus responsible for a group of diseases collectively known as PCV2 Associated Diseases (PCVAD). Variation in the incidence and severity of PCVAD exists between pigs suggesting a host genetic component involved in pathogenesis. A large-scale genome-wide association study of experimentally infected pigs (n = 974), provided evidence of a host genetic role in PCV2 viremia, immune response and growth during challenge. Host genotype explained 64% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In the USMARC population, the genes overlapping QTL were identified in the five-SNP QTL windows extended by 300 kb in both directions (n = 222 windows) that explained the largest proportion of genetic variance for age at puberty (Nonneman et al, 2016b). Another portion of the array included SNP located in genes with ontologies associated with innate and adaptive immunity, and also SNP known to affect viral disease susceptibility (Walker et al, 2018). The immunity-related gene ontology terms were obtained from Ensemble BioMart tool (https://may2017.archive.ensembl.…”
Section: Design Of the Sowpro90 Snp Arraymentioning
confidence: 99%
See 3 more Smart Citations
“…In the USMARC population, the genes overlapping QTL were identified in the five-SNP QTL windows extended by 300 kb in both directions (n = 222 windows) that explained the largest proportion of genetic variance for age at puberty (Nonneman et al, 2016b). Another portion of the array included SNP located in genes with ontologies associated with innate and adaptive immunity, and also SNP known to affect viral disease susceptibility (Walker et al, 2018). The immunity-related gene ontology terms were obtained from Ensemble BioMart tool (https://may2017.archive.ensembl.…”
Section: Design Of the Sowpro90 Snp Arraymentioning
confidence: 99%
“…The SNP array also consisted of potential loss-of-function SNP (Keel et al, 2017) as well as DNA markers for age at puberty identified in the USMARC studies (Nonneman et al, 2016a). The scaffold SNP incorporated in the SowPro90 obtained from the Porcine SNP60 BeadArray had a minor allele frequency > 0.05 in the UNL maternal crossbred data sets used for sow reproductive (Wijesena et al, 2017) and viral disease (Walker et al, 2018) research. The SowPro90 was also supplemented with SNP included in the Neogen Porcine GGPHD Array (Neogen Genomics, Lincoln, NE) if they overlapped the top 1% of the QTL for age at puberty (Wijesena et al, 2017) and SNP from the Affymetrix Axiom Pig High Density (PigHD) Array (Groenen, 2015; Thermo Fisher Scientific Inc. Waltham, MA) located in the Swine Leukocyte Antigen complex II locus ( Table 1).…”
Section: Design Of the Sowpro90 Snp Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…Association between phenotypic traits and major DNA markers, selected based on this research and previous studies (Boddicker et al, 2012;Serão et al, 2014;Walker et al, 2018), was assessed using a linear mixed model fit by JMP Pro 13.1 (SAS Inst. Inc.).…”
Section: Genome-wide Association Analysesmentioning
confidence: 99%